Keluarga sebagai Madrasah Pertama Anak (Memaksimalkan Peran Orang Tua dalam Perkembangan Anak Usia 1-4 Tahun, T.A. 2019/ 2020) - Khairi Khairi (STAI Auliaurrasyidin Tembilahan, 2020)
Family is the nearest environment the children have. It belongs to the first and primary educational instution for them learn and grow. All developmental aspects of the children – include values of relious and moral, physical motor, cognitive, language, social-emotional, and arts – should be stimulated and supported by parents especially in family. The parents should be able to know those all aspects, so they can stilumate them appropriately. Parents play a vital role in stilumating and guiding them grow and develop. Good experience with parents they have will bring them to easily interaction with their environment. Children at 1-4 years old need people like parents to stimulate and to bring them model of good behavior, so they can survive in their future.